2014
DOI: 10.3109/01612840.2013.871088
|View full text |Cite
|
Sign up to set email alerts
|

Patients Subject to High Levels of Coercion: Staff's Understanding

Abstract: Measures to keep staff and patients safe (containment) frequently involve coercion. A small proportion of patients is subject to a large proportion of containment use. To reduce the use of containment, we need a better understanding of the circumstances in which it is used and the understandings of patients and staff. Two sweeps were made of all the wards, spread over four hospital sites, in one large London mental health organization to identify patients who had been subject to high levels of containment in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…As such, this study supports others demonstrating 'therapeutic poverty' in UK psychiatric nursing practice. 87 4. Non-standard transfer: move of the patient to another ward providing more secure or intensive care in some fashion, perhaps in a private hospital or in a neighbouring trust, or via a secure rehabilitation ward or a forensic ward of some type.…”
Section: Availability and Escalation Pathwaysmentioning
confidence: 99%
“…As such, this study supports others demonstrating 'therapeutic poverty' in UK psychiatric nursing practice. 87 4. Non-standard transfer: move of the patient to another ward providing more secure or intensive care in some fashion, perhaps in a private hospital or in a neighbouring trust, or via a secure rehabilitation ward or a forensic ward of some type.…”
Section: Availability and Escalation Pathwaysmentioning
confidence: 99%
“…If so, in which situations should coercion be considered acceptable, and which particular types of coercion are safe and effective? This debate is also relevant for the field of residential youth settings, because restraint and seclusion continue to be used on youth in residential settings at higher rates than on adults in care (Bowers et al 2014;LeBel et al 2010). Researchers have found that restraint is used on 30 % of youth in juvenile facilities, schools, and residential treatment programs (Kennedy and Mohr 2001), and that noncompliance is often the starting point of coercive cycles (Smith and Bowman 2009).…”
Section: Coercionmentioning
confidence: 99%
“…Less qualified staff also consider annoying behavior of patients to be an adequate reason for restraint (Gelkopf et al 2009). It has been suggested (Bowers et al 2014;Gelkopf et al 2009;Nelson et al 2010) that these results may stem from a lack of tools for coping with annoying actions and insufficient knowledge of psychopathology, which could explain the patients' annoying behavior. Researchers (Van der Helm et al 2006) also pointed to fear of losing control and lack of leadership, which can lead to a loss of patience and an inability to cope with the situation without physical restraints.…”
Section: Staff Selectionmentioning
confidence: 99%
“…Perceptions, attitudes, and emotional reactions of staff and patients are considered to affect interactional behavior preceding aggressive incidents (1519). An example for problematic behavior given by Bowers et al (20) describes health care professional frustration due to repetitive requests at inappropriate times concerning a trivial item. The type of management that is used to deal with problematic patient behavior influences the interactional response and may lead to an escalation (8, 2123).…”
Section: Introductionmentioning
confidence: 99%
“…Escalation can, e.g., be triggered by a controlling (15, 24, 25), over-confident, and punitive management approach by staff (2629). In addition, restrictive regiments like limiting patients' freedom or denying patients' requests appear to be an essential antecedent of aggressive behavior (10, 14, 20, 30, 31).…”
Section: Introductionmentioning
confidence: 99%